Adjustable Cortical Fixation Device for Quadriceps Tendon Repair: A Cadaveric Biomechanical Study. Issue 1 (28th January 2021) - Gould, Heath P.; Rate, William R.; Abbasi, Pooyan; Mistretta, Katherine L.; Hammond, Jason W.
Background: Adjustable cortical fixation devices have demonstrated utility in orthopaedic applications, such as ankle syndesmosis repair. Purpose: To assess the cyclic gap formation of a quadriceps tendon repair technique using an adjustable cortical fixation device compared with repair with knotless suture anchors and suture tape, a modification of conventional suture anchor repair. Study Design: Controlled laboratory study. Methods: Eight fresh-frozen matched pairs of cadaveric knees were used. Specimens in each pair were randomized to undergo either modified suture anchor repair (control) or adjustable cortical fixation repair. The control repair was performed as previously described. The experimental repair was performed using 2 No. 2 FiberWire sutures placed into the quadriceps tendon in a running locked Krackow configuration and 2 adjustable loop devices passed through transosseous tunnels. The lagging strands of the devices were tensioned to seat the cortical fixation buttons at the inferior patellar pole and then tied to the free Krackow strands at the superior pole to complete the repair. The mean plastic gap (permanent tendon displacement that did not recover with cyclic extension) and mean maximum gap (peak displacement that occurred with cyclic knee flexion and partially recovered with extension) were evaluated during cyclic loading for 500 cycles of full knee extension to 90° of flexion. Results: At all testing intervals, the mean plastic gap was significantly smaller for the cortical fixation group versus the suture anchor group ( P < .02). Similarly, the mean maximum gap was significantly smaller for the cortical fixation specimens at all testing intervals ( P < .01). After cyclic loading, the mean maximum gap was significantly smaller in the cortical fixation group (4.80 ± 1.56 mm) versus the suture anchor group (8.47 ± 1.47 mm; P = < .001). The mean plastic gap was also significantly smaller in the cortical fixation versus the suture anchor group (3.25 ± 1.10 mm vs 6.57 ± 1.62 mm, respectively; P = < .001). Conclusion: Quadriceps tendon repair using an adjustable cortical fixation device demonstrated superior biomechanical properties in cyclic displacement testing compared with repair using the suture anchor technique. Clinical Relevance: These results suggest that an adjustable cortical fixation device is a biomechanically viable alternative for quadriceps tendon repair.